Strengthening the Economy of the Tengger Community Based on Ecotheology Through Conservation and Educational Tourism - Abdul Hakim; Mas Adah; Nurul Lathifah; Achmad Room Fitrianto; Faridatus Shobiyah; Luthfiyah Syafa Faizzah (GUYUB: Journal of Community Engagement, 2026)
Baladaun Conservation is a customary forest in Tosari Village, Pasuruan, managed collectively by the Tengger community as an expression of ecological stewardship and spiritual responsibility. Rooted in an eco-theological worldview, nature is regarded as a sacred trust linking humans, the environment, and the divine. Despite its strong ecological and cultural potential for educational tourism, the community faces challenges in institutional capacity, marketing, halal certification, and product distribution. This community service program applies the Asset-Based Community Development (ABCD) approach to strengthen local economic capacity through participatory asset mapping, stakeholder engagement, and capacity-building initiatives. The program outcomes demonstrate measurable improvements. A total of 17 community members are now actively involved in tourism services, while 12 local producers engage in value-added processing of coffee and honey. Approximately 35% of participating households reported additional income sources beyond traditional agriculture. Digital promotion increased outreach, generating over 1,200 online interactions, while several enterprises successfully obtained Business Identification Numbers (NIB) and initiated halal certification. In addition, conservation efforts included the planting of 500 tree seedlings and the establishment of waste management practices. These results indicate enhanced economic diversification, improved institutional capacity, strengthened market access, and reinforced environmental conservation based on Tengger cultural value